Hubungan Antara Leucorrhea, Pola Seksual, Dan Personal Hygiene Dengan Kejadian Ketuban Pecah Dini : The Relationship Between Leucorrhea, Sexual Pattern, and Personal Hygiene with Premature Rupture of Membranes - Mayang Sari, Intan (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Premature rupture of membranes (PROM) is a condition in which the membranes rupture before delivery. Premature rupture of membranes can cause several problems for the mother as well as for the fetus. The purpose of this study was to determine the relationship between vaginal discharge, sexual patterns, and Personal Hygiene with the incidence of premature rupture of membranes at Cianjur Dr. Hafiz Hospital 2021. Methods: This research is a quantitative type with an analytic nature. The research design used is a cross-sectional or cross-sectional study. The population in this study were pregnant women at Cianjur Dr. Hafiz Hospital as many as 729 people and from the results of the calculation of the sample in this study were as many as 88 respondents. Determination of the sample in this study using the purposive sampling technique. Results: The research instrument used a questionnaire. Data analysis using chi-square test.  The results are based on the study of the relationship between Leucorrhea, a p-value = 0,000 was obtained. The sexual pattern obtained p-value = 0,004 and Personal hygiene with the incidence of premature rupture of membranes at Cianjur Dr. Hafiz Hospital in 2021. Discussion: There is a relationship between vaginal discharge, sexual patterns, and Personal Hygiene with the incidence of premature rupture of membranes at Cianjur Dr. Hafiz Hospital in 2021 Suggestions for hospitals to provide information to pregnant women during ANC related to preventing the occurrence of PROM events.